Transforming One‐Dimensional Nanowalls to Long‐Range Ordered Two‐Dimensional Nanowaves: Exploiting Buckling Instability and Nanofibers Effect in Holographic Lithography. (16th December 2013) - Li, Jie; Cho, Yigil; Choi, In‐Suk; Yang, Shu
<x xml:space="preserve">Abstract</x> Two‐dimensional nanowaves with long‐range order are fabricated by exploiting swelling‐induced buckling of one‐dimensional (1D) nanowalls with nanofibers formed in‐between during holographic lithography of the negative‐tone photoresist SU‐8. The 1D film goes through a constrained swelling in the development stage, and becomes buckled above the critical threshold. The degree of lateral undulation can be controlled by tuning the pattern aspect ratio (height/width) and exposure dosage. At a high aspect ratio (e.g., 6) and a high exposure dosage, nanofibers (30–50 nm in diameter) are formed between the nanowalls as a result of overlapping of low crosslinking density regions. By comparing experimental results with finite‐element analysis, the buckling mechanism is investigated, which confirms that the nanofibers prevent the deformed nanowalls from recovery to their original state, thus, leading to long‐range ordered two‐dimensional (2D) wavy structures. The film with nanowaves show weaker reflecting color under an ambient light and lower transmittance compared to the straight nanowalls. Using double exposure through a photomask, patterns consisting of both nanowaves and nanowalls for optical display are created.